2018
DOI: 10.1369/0022155417749828
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Glutamate Transporters in Mouse Liver, Kidney, and Intestine

Abstract: Glutamate transport activities have been identified not only in the brain, but also in the liver, kidney, and intestine. Although glutamate transporter distributions in the central nervous system are fairly well known, there are still uncertainties with respect to the distribution of these transporters in peripheral organs. Quantitative information is mostly lacking, and few of the studies have included genetically modified animals as specificity controls. The present study provides validated qualitative and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…To shed some light on this issue, we analyzed the protein expression of both GLAST/EAAT1 and GLT-1/EAAT2 in liver tissue after CCl 4 treatment. The results described above revealed that as previously reported, GLT-1/EAAT2 is the main Glu transporter expressed in mouse liver (Utsunomiya-Tate et al, 1997;Berger and Hediger, 2006;Hu et al, 2018). The detection of GLT-1/ EAAT2 as several bands in CNS (∼70,150,and 190 kDa) and only one band in liver tissue (∼150 kDa) indicates that this higher molecular weight band might be corresponding to a multimeric fraction of the transporter.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To shed some light on this issue, we analyzed the protein expression of both GLAST/EAAT1 and GLT-1/EAAT2 in liver tissue after CCl 4 treatment. The results described above revealed that as previously reported, GLT-1/EAAT2 is the main Glu transporter expressed in mouse liver (Utsunomiya-Tate et al, 1997;Berger and Hediger, 2006;Hu et al, 2018). The detection of GLT-1/ EAAT2 as several bands in CNS (∼70,150,and 190 kDa) and only one band in liver tissue (∼150 kDa) indicates that this higher molecular weight band might be corresponding to a multimeric fraction of the transporter.…”
Section: Discussionsupporting
confidence: 85%
“…GLT-1/EAAT2 expression has been reported in rat and mouse liver tissues (Berger and Hediger, 2006;Hu et al, 2018) and recently GLAST/EAAT1 was also reported in a human hepatoblastoma cell line, HepG2 (Jiménez-Torres et al, 2020). FIGURE 2 | slices by immunohistochemistry using the same antibody as in western blot analyses.…”
Section: Glutamate Transporters Expression Is Altered In Liver Tissuementioning
confidence: 95%
See 1 more Smart Citation
“…EAATs are also found in peripheral tissues; for instance, EAAT3, originally known as EAAC1, was reported to have mRNA expressed in the liver, the intestine, the kidney and the heart of rabbits [ 14 ] . Lately, a low level of EAAT1 mRNA was identified in the mouse liver, kidney and intestine, with relatively a little higher EAAT2 in the liver, much higher EAAT3 at intestine and highest EAAT3 in the kidney [ 88 ] . Moreover, broad expression of EAAT5 in the liver, kidney, intestine, heart, lung and skeletal muscle of rats has been identified at both mRNA and protein levels [ 89 ] .…”
Section: Eaats and Cancersmentioning
confidence: 99%
“…Cysteine is the rate-limiting substrate for the synthesis of the antioxidant glutathione and its extracellular depletion is hypothesized to contribute to neurodegeneration. EAAT3 is also the dominant glutamate transporter in the intestines and provides nutrient absorption from the diet (Hu et al, 2018), but knockout animals appear to grow at a comparable rate to their litter mates (Peghini et al, 1997). The most remarkable initial observation from EAAT3 knockout mice was aminoaciduria due to the absence of EAAT3 in the kidneys (Peghini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%